Profiling Substrate Promiscuity of Wild-Type Sugar Kinases for Multi-fluorinated Monosaccharides. Issue 9 (17th September 2020) - Keenan, Tessa; Parmeggiani, Fabio; Malassis, Julien; Fontenelle, Clement Q.; Vendeville, Jean-Baptiste; Offen, Wendy; Both, Peter; Huang, Kun; Marchesi, Andrea; Heyam, Alex; Young, Carl; Charnock, Simon J.; et al.
Summary: Fluorinated sugar-1-phosphates are of emerging importance as intermediates in the chemical and biocatalytic synthesis of modified oligosaccharides, as well as probes for chemical biology. Here we present a systematic study of the activity of a wide range of anomeric sugar kinases (galacto- and N -acetylhexosamine kinases) against a panel of fluorinated monosaccharides, leading to the first examples of polyfluorinated substrates accepted by this class of enzymes. We have discovered four new N -acetylhexosamine kinases with a different substrate scope, thus expanding the number of homologs available in this subclass of kinases. Lastly, we have solved the crystal structure of a galactokinase in complex with 2-deoxy-2-fluorogalactose, giving insight into changes in the active site that may account for the specificity of the enzyme toward certain substrate analogs. Graphical Abstract: Highlights: Anomeric kinases screened for activity against fluorinated monosaccharides Phosphorylation of 11 substrates including di- and tetrafluorinated sugars were observed Crystal structure of BiGalK shows active-site interactions with 2FGal This work has practical applications in medicinal chemistry and chemical biology Abstract : Keenan, Parmeggiani et al. report the exploitation of wild-type anomeric sugar kinases to access fluorinated monosaccharide-1-phosphates. They demonstrate the effective phosphorylation of 11 different fluorinated monosaccharides, including di- and tetrafluorinated sugars. This work has practical applications in medicinal chemistry and chemical biology, particularly in the synthesis of fluorinated glycans.